Staying in or Dropping Out of Elite Women's Football-Factors of Importance - Ingrid Amalie Hoftun Bjerksæter; Pål Arild Lagestad (Frontiers Media S.A., 2022)
The average age of elite women footballers in Norway is 22.7 years, significantly lower than that of elite male footballers in Norway (26.5). This study examines the factors leading to elite female footballers ending their careers at a relatively young age, and those factors influencing other female elite players to continue. Semi-structured interviews were conducted with five female elite players who had ended their career at the age of 19-24, and four who were still active (age 26-31). Based on the age of the informants who had ended their career and the informants who were still active, this study defines "young age" as <25years of age. The female elite players experiences were analyzed and discussed in relation to earlier research. The results of the study show that the same factors affecting the early end of a career, also had an impact on continuing the career in the Norwegian top league, beyond the average age. A low level of internal and external motivation, poor financial circumstances, high stress load, long injury breaks, lack of playing time and other priorities, are all factors leading elite players to end their football careers at a young age. These factors are increasingly being addressed in relation to still active elite players, and this has an impact on the length of their playing career. Like earlier research, this study indicates that the emergence of Norwegian women's football in recent years has helped to improve conditions for being female elite players in the professional leagues in Norway.